Security Analysis of Wireless Local Area Network (WLAN) Network with the Penetration Testing Method - Fikriyadi Fikriyadi; Ritzkal Ritzkal; Bayu Adhi Prakosa (Jurnal Mantik, 2020)
Wireless Local Area Network (WLAN) is an alternative in overcoming cabling problems in a local network. Often wireless network security that is installed still uses vendor default settings such as SSID, IP Address, remote management, DHCP enabled, frequency channels, without encryption, even user or password for wireless administration. How does a strong WLAN security system work? The most common security system applied to wireless networks at this time is starting from securing access points by applying the MAC Filtering concept, using WPA / WPA2-PSK security keys, and RADIUS server authentication. To see the quality of wireless LAN network security, how do you analyze the test of the existing security system in the network. The method that can be used in evaluating wireless networks is by testing the system by simulating forms of attacks on wireless networks with the Penetration Testing method. By carrying out 4 stages of research using the penetration testing method (i) the planning stage, (ii) the discovery stage, (iii) the attack stage and (iv) the report stage, from the attack stage (Cracking The Encryption, Bypassing MAC Address, Attacking The Infrastructure and MITM ) using Kali Linux got the results of four types of attacks carried out, only one of which was failed, namely the cracking attack type of the encryption on the RADIUS server due to using captive portal authentication